1.5 mile run time and body mass predict 8 mile loaded march performance, irrespective of sex. Issue 2 (February 2019) - Coakley, S.L.; Myers, S.D.; Walker, E.F.; Hale, B.; Jackson, S.; Greeves, J.P.; Roberts, R.; Blacker, S.D.
Abstract: Objectives: To develop a statistical model to predict 8 mile Loaded March (LM) performance and quantify differences in physical characteristics for men and women British Army Personnel. Design: 135 trained soldiers (87 men; 48 women) completed two sessions, seven days apart. Methods: Session 1: Participants' stature, body mass, Fat Free Mass (FFM) [by dual-energy X-ray absorptiometry], Single Lift (SL), Water Can Carry (WCC), and 1.5 mile run performance were measured. Session 2: Participants completed an 8 mile LM, carrying 25 kg (4 miles paced and 4 miles individual best effort). Sex differences were compared using independent samples t-tests and 8 mile LM performance time was predicted using various multiple linear regression analysis: hierarchical forced entry multiple ordinary least squares, principal component and ordinary least products. Results: A combination of 1.5 mile run time and body mass were the strongest predictors of 8 mile LM time ( R 2 = 0.71; SEE = 4.17 min; p < 0.001). Including stature, FFM, sex, SL score, or WCC score did not further improve predictions ( p > 0.05). Compared to women, men had faster mean 1.5 mile run and LM times, greater body mass and total FFM and higher SL and WCC scores ( p < 0.001), however some women outperformed men. Conclusion: 1.5 mile run time and body mass predict 8 mile LM performance with no further improvement gained in the model by including sex as a variable.